탄소 담지 Pd 촉매상에서 고농도 아세 틸렌의 선택적 수소화 반응에 대한 연구 - 황석영 (The Graduate School, Ajou University, 2024)
아세틸렌을 에틸렌으로 선택적으로 수소화시키는 촉매 공정에 대한 대부분의 연구는 나프타 분해 공정의 후단에서 생성되는 에틸렌 기류에 미량 존재하는 아세틸렌을 제거하는 목적에 초점을 맞추어 진행되고 있다. 아세틸렌을 제거하려는 주된 목적은 아세틸렌이 고분자 합성 공정에서 촉매독으로 작용해 낮은 순도의 고분자 물질이 만들어지기도 한다. 아세틸렌 수소화 반응에서는 주로 Pd 가 담지된 불균일계 촉매가 쓰이고, 에틸렌의 선택도를 높이기 위해 여러 조축매가 첨가되기도 한다. 아세틸렌이 수소화되는 과정에서 올리고머화 반응에 의해 Green oil 이라는 물질이 만들어지는데, 이는 촉매 활성 표면을 덮어서 아세틸렌 전환율을 저하할 뿐만 아니라 수소의 저장체로 사용되어 피드의 분율을 바꾸고 에틸렌 선택도에도 악영향을 미친다. 생성된 Green oil 이 촉매 기공 안에서 빠르게 배출될 수 있도록 중형 기공성을 갖는 친수성 지지체를 사용해야 한다. 이번 연구에서는 Pd 가 담지된 불균일계 촉매의 서로 다른 지지체 CMK-3, short CMK-3(sCMK-3), Activated Carbon(AC), Graphite, Mesoporous Carbon(Meso-C), Graphite Nanofiber(GNF), Carbon Nanotube(CNT)에 따른 아세틸렌 수소화 반응을 수행하였다.|Most research on the catalytic process for selective hydrogenation of acetylene to _x000D_ ethylene has been focused on eliminating trace amounts of acetylene in the ethylene _x000D_ stream produced at the tail-end of the naphtha cracking process. The primary _x000D_ motivation behind acetylene removal lies in its role as a catalyst poison in the _x000D_ polymer synthesis process, leading to the production of low-purity polymer materials. _x000D_ The acetylene hydrogenation reaction typically employs a heterogeneous catalyst _x000D_ containing Pd, and various promoters are introduced to enhance ethylene selectivity. _x000D_ During acetylene hydrogenation, the formation of an oligomer material known as _x000D_ green oil occurs through oligomerization reactions. The green oil not only reduces _x000D_ acetylene conversion by covering the catalytic active sites but also serves as a _x000D_ hydrogen reservoir, altering the feed composition and reducing the ethylene _x000D_ selectivity. It is essential to use hydrophilic and mesoporous support to facilitate the _x000D_ rapid removal of generated green oil from the catalyst pores. In this study, acetylene _x000D_ hydrogenation was conducted using a Pd catalyst with different supports CMK-3, _x000D_ short CMK-3 (sCMK-3), activated carbon (AC), graphite, mesoporous carbon _x000D_ (Meso-C), graphite nanofiber (GNF), and carbon nanotube (CNT).
학위논문(석사)--에너지시스템학과,2024. 2
Keywords: 그린 오일; 아세틸렌 수소화; 에틸렌; 탄소 동소체; 팔라듐 불균일계 촉매